Decrease in the proportion of CD24hiCD38hi B cells and impairment of their regulatory capacity in type 1 diabetes patients. (3rd January 2020) - Wang, Y; Qin, Y; Wang, X; Zhang, L; Wang, J; Xu, X; Chen, H; Hsu, H-T; Zhang, M
Summary: B10 cells restore immune balance by producing interleukin (IL)-10. Impaired B10 cell responses are related to numerous autoimmune diseases. However, the function of B10 cells in type 1 diabetes (T1D) patients is controversial. We hypothesized that there are numerical and functional defects of B10 cells in T1D. Sixty-two patients with T1D and 74 healthy volunteers were included in our study. We showed that B10 cells in human peripheral blood belong to a CD24 hi CD38 hi B cell subpopulation. CD24 hi CD38 hi B cells from healthy individuals possessed regulatory capacity, suppressed interferon (IFN)-γ, tumor necrosis factor (TNF)-α and IL-17A production and promoted IL-4 production and forkhead box protein 3 (FoxP3) expression in CD4 + T cells through an IL-10-dependent mechanism. Compared to healthy controls, B10 cell percentages in T1D were significantly lower (5·6 ± 3·5 versus 6·9 ± 3·3%; P <  0·05), produced less IL-10 (15·4 ± 4·3 versus 29·0 ± 4·5%; P <  0·001) and lacked regulatory capacity. In addition, Pearson's correlation analysis showed that the frequency of circulating B10 cells was negatively correlated with the frequency of CD4 + IFN-γ + and CD4 + TNF-α + T cells ( r = −0·248 and r = −0·283, P = 0·008 and P = 0·017, respectively), positively correlating with the frequency of CD4 + CD25 + FoxP3 + T cells ( r = 0·247, P = 0·001). These data offer direct proof that there is a deficiency of circulating CD24 hi CD38 hi B cells in peripheral blood of patients with T1D, which participate in the T1D immune imbalance involved in the development of T1D. Graphical Abstract: